2014
DOI: 10.1111/hcre.12046
|View full text |Cite
|
Sign up to set email alerts
|

Violent Movies and Severe Acts of Violence: Sensationalism Versus Science

Abstract: Violent media has often been blamed for severe violent acts. Following recent findings that violence in movies has increased substantially over the last few decades, this research examined whether such increases were related to trends in severe acts of violence. Annual rates of movie violence and gun violence in movies were compared to homicide and aggravated assault rates between the years of 1960 and 2012. Time series analyses found that violent films were negatively, although nonsignificantly, related to ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 66 publications
1
14
2
3
Order By: Relevance
“…We also suggest that policymakers, scholars and child advocates exert great caution in asserting conclusive links between war theme toys and behavioural problems, as evidence does not support such contentions. The apparent absence of association between playing with war toys and later real aggression is in line with recent data questioning the long‐term harmfulness of similarly themed television (Schwartz & Beaver, ), movies (Markey et al, ) or video games (Przybylski & Mishkin, ). Attraction to some aggressive themes in play and media may be developmentally normal (Olson, ), and restricting such play may have more detrimental impact than positive.…”
Section: Discussionsupporting
confidence: 80%
“…We also suggest that policymakers, scholars and child advocates exert great caution in asserting conclusive links between war theme toys and behavioural problems, as evidence does not support such contentions. The apparent absence of association between playing with war toys and later real aggression is in line with recent data questioning the long‐term harmfulness of similarly themed television (Schwartz & Beaver, ), movies (Markey et al, ) or video games (Przybylski & Mishkin, ). Attraction to some aggressive themes in play and media may be developmentally normal (Olson, ), and restricting such play may have more detrimental impact than positive.…”
Section: Discussionsupporting
confidence: 80%
“…The examination undertaken here and in the more comprehensive analysis originally published (Markey et al, ) finds no grounds for even a hypothesis that increased depiction of violence and guns in movies over time stimulates young people to real homicide and shootings. Any other random factor, such as the average length of movies, proves just as invalid a predictor when tested.…”
Section: Linking Violence In Films To Violence By Youthcontrasting
confidence: 54%
“…We thank Bushman, Romer, and Jamieson () for taking the time to comment on our article Violent Movies and Severe Acts of Violence : Sensationalism Versus Science (Markey, French, & Markey, ). We believe an open dialogue is the best way to address the differences that exist between scientists on both sides of the debate concerning the role of the media in real‐world violence.…”
mentioning
confidence: 99%
“…Consistent with previous research reviewed above, we found that social support and personality are relevant for understanding the effect of video games on mental health, and these results fit within the emerging literature finding limited harm of video game play (Ferguson, ). The influence of these psychosocial factors and historical overinterpretation of the modest negative effects of media on mental health (Markey, French, & Markey, ) should be considered in clinically evaluating veterans’ game playing.…”
Section: Discussionmentioning
confidence: 99%